Big fish (and a smallish skate) eat small fish: diet variation and trophic level of Sympterygia acuta, a medium-sized skate high in the food web - Barbini, Santiago Aldo (2015)
The bignose fanskate, Sympterygia acuta, is a small-to-medium-sized species endemic to shallow coastal waters of the Southwest Atlantic. Sympterygia acuta displays a clear seasonal reproductive cycle, characterized by maximum egg-laying activity in spring and hatching in summer. We hypothesized that diet and feeding activity change with maturity stage and season and that, given its smallish size, the trophic level is low. Using a multiple-hypothesis modeling approach, the diet of S. acuta in relation to sex, body size, maturity stage, region (i.e. north and south) and season was analysed; and a potential relationship between feeding activity and the seasonal reproductive cycle was assessed. Sympterygia acuta fed on a broad spectrum of prey, but teleosts were more important (47.97% index of relative importance, %IRI), followed by decapods (39.84%IRI), cumaceans (8.31%IRI) and isopods (1.89%IRI). Maturity stage was a strong determinant of the ontogenetic diet shift of S. acuta, and relationships between number of prey consumed with season and region were found.. Feeding activity was higher in the cold season than in the warm season, and was less important in the south region than in the north region. Unexpectedly, the specific trophic level was high (3.87). Sympterygia acuta shifts its diet with maturity stage, possibly by a combination of an improved ability to capture prey and a change in energy demand of mature individuals. Despite being a small-to-medium-sized skate, S. acuta showed a trophic level similar to that of large-bodied marine predators. It reduces its feeding activity seasonally because in the warm season this species may experience an increased predation risk from large sharks.